Hubungan Pengetahuan dan Sikap dengan Perilaku Pencegahan Filariasis di Kecamatan Cilimus Kabupaten Kuningan - Nissa Noor Annashr; Fathi Muhamad Rahmadi (Loka Litbang Kesehatan Pangandaran, 2021)
Lymphatic filariasis is a chronic infectious disease caused by parasitic nematodes. The worm can damage the human lymphatic system gradually then causing enlargement of the limbs, breasts and genitalia. Kuningan is an endemic regency for filariasis in West Java Province. Cilimus District was in the 2nd position as a district with the highest filariasis cases in Kuningan in 2017. This research was conducted in Cilimus District from May to June 2018 using a cross-sectional design. The population was all households in the Cilimus District with a sample size of 106 people who were taken using a simple random sampling technique. The independent variables studied were knowledge and attitudes regarding the prevention of filariasis, the dependent variable was the filariasis prevention practices. Data collection was carried out by interview using a questionnaire. Data analysis was performed by univariate and bivariate (chi-square test). The results showed that some respondents had good knowledge and positive attitudes about the prevention of filariasis (50%). The description of respondent practices showed that 82.1% of respondents took filariasis drug, 62.3% of respondents had the habit of using mosquito repellent, only 4.7% of respondents used mosquito nets, 49.1% of respondents put gauze wire, 47.2% of respondents did not have a habit of hanging clothes. The results of categorizing behavioral variables were found that more than half of the respondents (52.8%) had implemented good prevention practices. The results of the bivariate analysis showed that there was a significant relationship between knowledge and attitude with filariasis prevention practices (p <0.05).